Rotaxane-branched radical dendrimers with TEMPO termini. Issue 12 (20th January 2022) - Peng, Zhiyong; Xu, Xiao-Qin; Wang, Xu-Qing; Shi, Xueliang; Wang, Wei; Yang, Hai-Bo
Abstract : The precise synthesis of novel rotaxane-branched radical dendrimers with up to 24 TEMPO radicals as termini was achieved. Abstract : The precise synthesis of novel rotaxane-branched radical dendrimers Gn-TEMPO ( n = 1–3) with up to 24 TEMPO radicals as termini was successfully achieved, from which nanoparticles with a good longitudinal relaxivity were further prepared, thus making them potential candidates as promising contrast agents for magnetic resonance imaging.